Handbook of Politics State and Society in Global Perspective - Leicht, Kevin T.; Jenkins, J. Craig; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Kevin T. Leicht, The University of Iowa, Iowa City, IA, USA J. Craig Jenkins, The Ohio State University, Columbus, OH, USA Political sociology is the interdisciplinary study of power and the intersection of personality, society and politics. The field also examines how the political process is affected by major social trends as well as exploring how social policies are altered by various social forces. Political sociologists increasingly use a wide variety of relatively new quantitative and qualitative methodologies and incorporate theories and research from other social science cognate disciplines. The contributors focus on the current controversies and disagreements surrounding the use of different methodologies for the study of politics and society, and discussions of specific applications found in the widely scattered literature where substantive research in the field is published. This approach will solidly place the handbook in a market niche that is not occupied by the current volumes while also covering many of the same theoretical and historical developments that the other volumes cover. The purpose of this handbook is to summarize state-of-the-art theory, research, and methods used in the study of politics and society. This area of research encompasses a wide variety of perspectives and methods that span social science disciplines. The handbook is designed to reflect that diversity in content, method and focus. In addition, it will cover developments in the developed and underdeveloped worlds.
Introduction: The Study of Politics Enters the Twenty-First Century -- Introduction: The Study of Politics Enters the Twenty-First Century -- Theory in the Study of Politics -- Institutional Theory -- Redesigning the State, Reorienting State Power, and Rethinking the State -- Public Opinion, Public Policy, and Democracy -- Democracy, Professions and Societal Constitutionalism -- Power, Politics, and the Civil Sphere -- On the Origins of Neoliberalism: Political Shifts and Analytical Challenges -- Transboundary Politics -- Elite Theory and Elites -- Conflict Theory -- When and Where Class Matters for Political Outcomes: Class and Politics in a Cross-National Perspective -- Political Change and Transformation -- Social Movements and Contentious Politics -- Political Violence as an Object of Study: The Need for Taxonomic Clarity -- Corporations, Capitalists, and Campaign Finance -- States and Economic Development -- Gender, Politics, and Women's Empowerment -- Globalization and Collective Action -- Cultural Analysis of Political Protest -- Religion and Post-secular Politics -- Space and Politics -- Politics and the Environment -- Politics as a Cultural Phenomenon -- Urban Politics -- Democracy and Democratization -- Authoritarian State and Contentious Politics -- Mass Media and Democratic Politics -- Elections and Voting -- The Politics of Economic Inequality -- The Political Sociology of Criminal Justice -- Methods in the Study of Politics -- Comparative-Historical Methodology in Political Sociology -- Multilevel Models -- Event History Methods -- Social Networks and Political Analysis -- Time Series Analysis of Political Change.
Keywords: Social sciences; Social Sciences; Sociology, general; Political Science, general